Desenvolvimento do sistema do capital e teorias de transição em Trotski e Mészáros - Gonçalves, Mauricio Bernardino [UNESP] (2015)
From 2008 until now, with the outbreak of the most important economic crisis since 1929, the discourse and the neoliberal ideology had lost even more strength, once the state has proved to be the ultimate guarantor of the capital system in a global level. The social problems worldwide that are on the roots of the crisis pile up without positive outlook for its resolutions. Beside this, the possibility of a social alternative order to capital and the theoretical-political legacy of Karl Marx are now, although timidly, being again debated. From this scenario, the issue of post-capitalist transition, and post-capital, arises, with the intensification of the crisis, as a very important problem for theories of substantive social changes. The work thus investigates two of them: the permanent revolution from Leon Trotski and the struggle beyond capital from István Mészáros, taken as representative of the social theory inspired by Marx and produced in the last century on the issue. While the first became involved with the repercussions - and detours - of the main practical experience of post-capitalist transition in the 20th century, the second assesses the shortcomings of that experience and the requirements for a general theory of transition. Here, we consider the problem of transition having the question of the state as one of its main focus. Trotski's theory of permanent revolution has different moments but as a whole reaffirms - incorporating some specific elements - the essential characteristics for the problem of the state and transition given from the classics of marxist social theory. However, working with a methodology and a original perspective on the totality category - which opens a field unexplored for social changes theories -, he leaves a legacy of great validity on the subject. The second, in turn, moves on directions and approaches insufficiently developed until now - in a sense shifting the focus of the ...